DIFFERENTIAL LEARNING BASED ON INFORMATION AND COMMUNICATION TECHNOLOGY: EXPERIENTIAL PRACTICE IN ISLAMIC EDUCATION - Adawiyah, Rabiatul; Nahar, Syamsu (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This research was conducted to analyze the implementation of differentiated learning based on information and communication technology in Islamic Religious Education lessons at SMK Skylandsea Yappsu Tanjung Morawa, which includes three main aspects, namely content differentiation, process differentiation and product differentiation. The research method used in this research is a qualitative method to be able to explain the data obtained in more depth, and the type of research is field research. The research approach was carried out using a case study approach. The data collection techniques used were observation, interviews and documentation studies. The data obtained was analyzed using data collection techniques, data reduction, data presentation and drawing conclusions. The results of this research are that Islamic education teachers at SMK Skylandsea Yappsu Tanjung Morawa have implemented differentiated learning components well, namely content differentiation, process differentiation and product differentiation, as well as being integrated with information and communication technology-based media. The implementation of differentiated learning was also adapted to the diversity of students. With this research, understanding regarding the implementation of differentiated learning based on information and communication technology in Islamic education lessons can become broader, so that it can help in formulating effective strategies.